A Legal Assistance In Criminal Action Trial Process - Akhmad Mufasirin; Aryani Witasari (Law Development Journal, 2021)
The purpose of this study was to analyze the form of legal aid in the criminal trial process. To analyze the forms of legal assistance provided by the Legal Aid Institute for victims. To analyze the obstacles to legal aid in the criminal trial process and its solutions. The method used by the researcher is a sociological juridical approach and the specifications in this study include analytical descriptive. Based on the results of the research that the form of legal assistance in the criminal trial process is to accompany the suspect/defendant at every level of examination, especially the level of prosecution and trial of criminal acts, so that human rights are guaranteed, during and after the trial and seek diversion of criminal cases so that the perpetrators of criminal acts get their rights. The forms of legal assistance that can be provided to victims by LBH, in the criminal justice process, start from assistance carried out when the victim starts reporting the case to the police until the case is decided in court. Constraints: In practice, the provision of legal aid that has been applied is only limited to the provision of legal aid as mandated by Article 56 of the Criminal Procedure Code. In the appointment of legal counsel for the Defendant based on the mandate of Article 56 of the KUHAP in the event that the Defendant is incapacitated who is threatened with a sentence of five years or more who does not have his own legal advisor, Judges often make stipulations on the appointment of legal counsel without knowing in advance whether the defendant is economically capable or not. Solution: Provide information on Posbakum services for the Defendant in the District Court. In this case, this can be done by placing an information board on the Posbakum service in front of the District Court Detainee or by providing a pamphlet containing information on the Posbakum service in the detention room.